Keputusan Pedagang Dalam Penggunaan Jasa Pelepas Uang: Analisis Binary Logistic - Yukhe Prawesty Wirama Putri, Putu Diah; Meydianawathi, Luh Gede (E-Jurnal Ekonomi Pembangunan Universitas Udayana; Vol. 2, No. 2, Februari 2013 (pp. 63-118), 2013)
Using binary logistic techniques, this study aims to determine the effect of administration, duration of the process and guarantees the merchant's decision in the use of services of moneylenders. The results of analysis of 71 respondents indicate administration Kedonganan Fish Market, a long process and simultaneously guarantee a significant effect on the decision to use merchant services moneylenders. Partially, the administration had no significant effect, while the old process and guarantee a significant effect on the decision to use merchant services moneylenders. Use of moneylenders services pose a major risk for small traders. Convenient services moneylenders should be a picture of the formal financial institutions in more role to facilitate accessibility.
Keywords: administrative; binary logistic; insurance; decision; long process